CHARACTERIZATION OF TECHNOLOGY-DEPENDENT PATIENTS IN HOME CARE SERVICES - Cecília Maria Brondani; Lais Helena Ramos; Margrid Beuter; Melissa Agostini Lampert; Margot Agathe Seiffert; Jamile Lais Bruinsma (Revista de Enfermagem da Universidade Federal de Santa Maria, 2014)
Doi: 10.5902/2179769211063